Online social interaction community model for unmet needs of older people - Embarak, Farhat; Ismail, Nor Azman; Ghazali, Masitah; Mahmud, Murni; Othman, Nur Zuraifah Syazrah; Hassan, Layla; Said, Che Soh; Pang, Yee Yong; Alsayed, Alhuseen Omar (Little Lion Scientific, 2023)
Modern medicine and technology have enhanced the average life expectancy of a person, but this has not improved the quality of life for those who are getting older. Elderly persons struggle to take care of their fundamental requirements, and family members are unable to give them the attention they require. An online community based new method of communication and interaction for the elderly could be a solution to address the situation, however, there are difficulties observed with the elderly persons throughout the design stage. In order to address the unmet everyday needs of older adults, this study investigated the design methodology and design process for an online social interaction community (OnSocialCom). A conceptual model was proposed specifically for senior people who live alone and was based on social connectedness, social support models, structural Camberwell evaluation of need for the elderly theories, and 4W (What Where-WhenWho) models. Its application in the actual setting was investigated through empirical investigations involving users and experts. The developed model contains five modules; online social interaction, profile management, unmet needs interaction, unmet needs plan, and recommendation. Additionally, evaluation was performed during the design process by experts for review for review analysis to clarify the needs of the users and assist in optimising the functionality of the conceptual model.